Impacto Del Factor Iluminación Y Psicosocial En El Desempeño Laboral Del Personal De Apoyo Y Asistencia A La Educación. Caso: UPIICSA - Sánchez, María Guadalupe Obregón; Márquez, Misaela Francisco (European Scientific Journal, ESJ, 2018)
The adaptation of the work environment in organizations and companies, constitute the essential measures for the prevention of health risks of workers, and is carried out through adjustments and ergonomic studies. It seeks to identify the problems of workers related to their environment, work area, and occupational diseases. Visual problems, headaches, and fatigue are not unrelated to this study and can be derived from poor lighting in the work areas. This research provides the necessary information for the management of physical risks associated with lighting. This, however, ranges from detection and evaluation to some control strategies. The study was carried out within a college campus of the National Polytechnic Institute, in Mexico, which is not excluded from the impact of ergonomic factors. The most wellknown reaction to an inadequate psychosocial situation is stress. Currently, there are various approaches and theoretical models that have studied it. However, all of them have a common element: the relationship between work and the person. Health problems arise when the demands of work are not adapted to the needs, expectations or abilities of the worker or when he or she does not receive adequate compensation, or adequate attention on behalf of their superiors. Another psychosocial risk recognized in the practice of the management of psychosocial risks (without prejudice to its possible typecasting in other preventive disciplines such as ergonomics or safety) is the fatigue of the worker linked to the organization of working time, either due to excess of work time or a lack of rest. It is most commonly manifested in the forms of night work or shifts and in situations of repeated extensions of the workday or lack of proper rest between days. Whatever the case may be, these psychosocial risks usually manifest themselves in an interrelated manner. Stress is a factor that causes violence and vice versa, while fatigue is often accompanied by stressful situations, especially when it results from an excessive workload, monotonous or repetitive work, and lack of rest. Information was obtained regarding the psychosocial factors that are affecting some workers and which have a significant impact on their productivity, their well-being, and their emotional stability. It takes into account stress, economic factors, and internal factors among their co-workers. Ergonomics and productivity are defined so as to carry out the relationship between them, and in order to know the impacts it may have on the worker and on their workspace in the form of discomfort and inconveniences. Methodologically, a questionnaire was administered to a representative sample of workers and the information obtained was subsequently captured in the Statistical Package for Social Science (SPSS) program. The results and graphs were obtained to carry out the interpretation of the results and develop intervention strategies when required. The sum of the physical factor, illumination, and the psychosocial factor show that some of the workers are not comfortable in their job post, resulting to their low productivity.